Analisis Model Grover, Altman, Springate dan Zmijewski Dalam Memprediksi Financial Distress Pada Perusahaan Sektor Transportasi, Logistik, Real Estate, dan Property - Aulia Fatmawati; Ferdawati; Lisa Amelia Herman; Reni Endang Sulastri (Jurnal Akuntansi Keuangan dan Bisnis, 2023)
This final assignment aims to determine the financial condition of companies in the logistics transportation, real estate and property sectors listed on the Indonesia Stock Exchange for the 2018-2022 period, using a purposive sampling method with a total sample of 36 companies (180 data per company year). The type of data used is secondary data obtained from the company's financial reports. This research uses 4 financial distress analysis models, namely the Grover, Altman, Springate, and Zmijewski models. The results of this research show that the Grover and Altman model produces the same pattern, where the transportation and logistics sector is predicted to be in a distressed condition, while the real estate and property sector is predicted to be in a non-distressed condition. The Springate model produces a different pattern where the transportation logistics, real estate and property sectors are more dominantly predicted to be in distress. Meanwhile, the Zmijewski model for companies in the transportation logistics, real estate and property sectors is predicted to be in a non-distress condition. Overall, the transportation and logistics sector experienced distress of 67% and 34% for the real estate and property sectors.